2016
DOI: 10.1051/0004-6361/201526928
|View full text |Cite
|
Sign up to set email alerts
|

How can young massive clusters reach their present-day sizes?

Abstract: Context. The classic question that how young massive star clusters attain their shapes and sizes, as we find them today, remains to be a challenge. Both observational and computational studies of star-forming massive molecular gas clouds infer that massive cluster formation is primarily triggered along the small-scale ( 0.3 pc) filamentary substructures within the clouds. Aims. The present study is intended to investigate the possible ways in which a filament-like-compact, massive star cluster (effective radiu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 84 publications
3
32
0
Order By: Relevance
“…All the computed models are initially Plummer clusters with masses M cl (0) ≤ 5 × 10 4 M and half-mass radius r h (0) = 2 pc; r h (0) = 1 pc are also used for a few lower mass models. Such masses and sizes are typical for Galactic and Local Group YMCs (Banerjee & Kroupa 2016;Portegies Zwart et al 2010;Ryon et al 2015); considering the masses of GCs, they represent intermediatemass and open stellar clusters (see Sec. 1).…”
Section: Model Computationsmentioning
confidence: 99%
“…All the computed models are initially Plummer clusters with masses M cl (0) ≤ 5 × 10 4 M and half-mass radius r h (0) = 2 pc; r h (0) = 1 pc are also used for a few lower mass models. Such masses and sizes are typical for Galactic and Local Group YMCs (Banerjee & Kroupa 2016;Portegies Zwart et al 2010;Ryon et al 2015); considering the masses of GCs, they represent intermediatemass and open stellar clusters (see Sec. 1).…”
Section: Model Computationsmentioning
confidence: 99%
“…Many Herbig Ae/Be stars are found in this young massive cluster. Banerjee & Kroupa (2017) used N-body simulations to study the cluster size of young massive clusters. They found that the simulated results were much more compact than observed one.…”
Section: Appendixmentioning
confidence: 99%
“…Apart from a smooth distribution, 50% of the dust is distributed fractally. We adopted N = 32, D = 2.6, H = 5 for the hierarchically clumpy distribution, a standard dust-to-gas ratio of 0.01 as suggested by Whelan et al (2011), and a representative star-forming efficiency (SFE) of 33% following Banerjee & Kroupa (2017). The SFE sets the mass of residual ISM and thus of dust, after stars have been formed.…”
Section: Model Descriptionmentioning
confidence: 99%